As(V) Removal Capacity of Fecu Bimetallic Nanoparticles in Aqueous Solutions: The Influence of Cu Content and Morphologic Changes in Bimetallic Nanoparticles - Rubio-Campos, M; Baltazar-Rojas, S; Arancibia-Miranda, N; Arancibia-Miranda, N; Sepúlveda-Ortiz, P; Sepúlveda-Ortiz, P; Rojas-Núñez, J (Academic Press, 2018)
In this study, bimetallic nanoparticles (BMNPs) with different mass ratios of Cu and Fe were evaluated. The influence of the morphology on the removal of pollutants was explored through theoretical and experimental studies, which revealed the best structure for removing arsenate (As(V)) in aqueous systems. To evidence the surface characteristics and differences among BMNPs with different mass proportions of Fe and Cu, several characterization techniques were used. Microscopy techniques and molecular dynamics simulations were applied to determine the differences in morphology and structure. In addition, X-ray diffraction (XRD) was used to determine the presence of various oxides. Finally, the magnetization response was evaluated, revealing differences among the materials. Our cumulative data show that BMNPs with low amounts of Cu (Fe0.9Cu0.1) had a non-uniform core-shell structure with agglomerate-type chains of magnetite, whereas a Janus-like structure was observed in BMNPs with high amounts of Cu (Fe0.5Cu0.5). However, a non-uniform core-shell structure (Fe0.9Cu0.1) facilitated electron transfer among Fe, Cu and As, which increased the adsorption rate (k), capacity (qe) and intensity (n). The mechanism of As removal was also explored in a comparative study of the phase and morphology of BMNPs pre- and post-sorption. © 2018 Elsevier Inc.